## 9.1 - Solving Systems of Linear Equations by Substitution

##### Created by:

clownprincess753  on January 14, 2011

Pop out
No Messages

# 9.1 - Solving Systems of Linear Equations by Substitution

 Solve by substitution. y = 3x - 1 x + y = 11Answer) x + y = 11 = x + (3x-1) = 11 = 4x = 12 = x = 3 x + y = 11 = 3 + y = 11 = y = 11 - 3 = y = 8
1/8
Preview our new flashcards mode!

Order by

#### Math / Symbols

Solve by substitution.
y = 3x - 1
x + y = 11
Answer) x + y = 11
= x + (3x-1) = 11
= 4x = 12
= x = 3
x + y = 11
= 3 + y = 11
= y = 11 - 3
= y = 8
Solve by substitution.
x - 2y = 4
x - 3y = 6
Answer) x - 2y = 4 --> x = 4 + 2y
= (4 2y) - 3y = 6
= -y = 6 - 4
= y = - 2
x - 2y = 4
= x - 2(-2) = 4
= x = 0
Solve by substitution.
2 + y = 3x
6x - 5y = 8
Answer) 2 + y = 3x --> y = 3x - 2
= 6x - 5(3x-2) = 8
= 6x - 15x + 10 = 8
= -9x = 8 - 10
= x = 2/9
2 + y = 3x
= 2 + y = 3(2/9)
= y = 2/3 - 2
= y = -4/3
Solve by substitution.
y = 8x
-y + 2 = -7x
Answer) -y + 2 = -7x
= -(8x) + 2 = -7x
= -8x + 7x = -2
= x = 2
y = 8x
= y = 8(2)
= y = 16
Solve by substitution.
4x + 5y = 26
3x = y - 9
Answer) 3x = y - 9 --> y = 3x + 9
= 4x + 5 (3x+9) = 26
= 4x + 15x + 45 = 26
= 19x = 26 - 45
= x = -1
3x = y - 9
= 3(-1) = y - 9
= y = (-3) + 9
= y = 6
Solve by substitution.
y = 3x + 2
x + y = 14
Answer) x + y = 14
= x + (3x + 2) = 14
= 4x = 14 - 2
= x = 3
y = 3x + 2
= y = 3(3) + 2
= y = 11
Solve by substitution.
y = x - 7
x + y = 17
Answer) x + y = 17
= x + (x - 7) = 17
= 2x = 17 + 7
= x = 12
y = x - 7
= y = 12 - 7
= y = 5
Solve by substitution.
y = -3x
y - x = 24
Answer) y - x = 24
= -3x - x = 24
= -4x = 24
= x = -6
y = -3x
= y = -3(-6)
= y = 18

### First Time Here?

Welcome to Quizlet, a fun, free place to study. Try these flashcards, find others to study, or make your own.